(untitled) (Research, Society and Development, 2023)
Objective: To analyze the scientific literature about the importance of respiratory physiotherapists in the field of urgency and emergency in hospital networks. Methodology: The research was bibliographical involving articles published between the years 2009 and 2022 in electronic databases, databases from the Physiotherapy Evidence Database (PEDro), and Scientific Electronic Library Online (SciELO), and Literature Latin American and Caribbean Health Sciences (Lilacs) in scientific journals that contain the following descriptors: “respiratory physiotherapy”, “urgency and emergency unit”. Results and Discussions: 15 articles were selected for the sample in accordance with the inclusion and exclusion criteria determined in this research resulting from the data search, after analyzing the summaries of the 15 (articles, dissertations, periodicals), of which the reading and analysis of all and 05 were considered relevant to present the results and discussions of this research. The information was collected in a descriptive way and predisposed the data extraction stage: author, year, title, main results and conclusion. Conclusion: The physiotherapist has great relevance in the field of urgency and emergency and his work and his technical-scientific knowledge directly contribute to the treatment and prevention of circulatory, cardiopulmonary and muscular pathologies, enabling the reduction of possible clinical complications, the permanence of longer hospital stay and reducing hospital costs. The inclusion of the Physiotherapist in the multidisciplinary team in urgent and emergency units can favor care and treatment, reducing the risk of worsening the clinical condition of patients who remain hospitalized in these units for a long period.